From Biological Determination to Entangled Causation - Vecchi, D (Springer Netherlands, 2019)
Biologists and philosophers often use the language of determination in order to describe the nature of developmental phenomena. Accounts in terms of determination have often been reductionist. One common idea is that DNA is supposed to play a special explanatory role in developmental explanations, namely, that DNA is a developmental determinant. In this article we try to make sense of determination claims in developmental biology. Adopting a manipulationist approach, we shall first argue that the notion of developmental determinant is causal. We suggest that two different theses concerning developmental determination can be articulated: determination of occurrence and structural determination. We shall argue that, while the first thesis is problematic, the second, opportunely qualified, is feasible. Finally, we shall argue that an analysis of biological causation in terms of determination cannot account for entangled dynamics. Characterising causal entanglement as a particular kind of interactive causation whereby difference-making causes ascribable to different levels of biological organisation influence a particular ontogenetic outcome, we shall, via two illustrative examples, diagnose some potential limits of a reductionist, molecular and intra-level understanding of biological causation. © 2018, Springer Nature B.V.